2018
DOI: 10.1002/slct.201801181
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Phase Oxidation Reaction and Mechanism of p‐Diethylbenzene to p‐Ethylacetophenone with H2O2 in a Batch Reactor and a Fixed Bed Reactor

Abstract: Liquid‐phase oxidation of p‐diethylbenzene (PDEB) to p‐ethylacetophenone (EAP) with hydrogen peroxide (H2O2) catalyzed by 5Co/SBA‐15 in a batch reactor and a fixed bed reactor was investigated. Based on the analysis of compositions, a reasonable reaction mechanism was discussed. Results show whether in a batch reactor or a fixed bed reactor, a mixture of EAP, 1‐(4‐ethylphenyl)‐1‐ethanol (EPEA), p‐diacetylbenzene (PDAB), 4‐acetylbenzoic acid (AA) and terephthalic acid (TA) could be detected. The reaction mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…[6] Sánchez [7] found that Al-MCM-41 showed good catalytic activity in the acylation of ethylbenzene and ethyl acetate with the conversion of ethylbenzene and the selectivity of EAP of more than 40 %. Kenneth [8] used Ce(OTf) 4 (cerium (IV) triflate) as catalyst in acetonitrile solvent to carry out PDEB oxidation at room temperature. Under the condition that the molar ratio of catalyst to PDEB is 4 : 1 and the reaction time is 25 h, the yield of EAP is 61.3 %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Sánchez [7] found that Al-MCM-41 showed good catalytic activity in the acylation of ethylbenzene and ethyl acetate with the conversion of ethylbenzene and the selectivity of EAP of more than 40 %. Kenneth [8] used Ce(OTf) 4 (cerium (IV) triflate) as catalyst in acetonitrile solvent to carry out PDEB oxidation at room temperature. Under the condition that the molar ratio of catalyst to PDEB is 4 : 1 and the reaction time is 25 h, the yield of EAP is 61.3 %.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, EAP and EPEA are fine chemical intermediates, which has widely used in organic synthesis, medicine and cosmetics industries leading to large market demand and high research value [3] . Wang [4] studied the process of liquid phase oxidation of p ‐diethylbenzene (PDEB) to p ‐ethylbenzone (EAP) with hydrogen peroxide (H 2 O 2 ) catalyzed by 5Co/SBA‐15 in batch reactor and fixed bed reactor. It is concluded that the selectivity of EAP in fixed bed reactor is stable at about 68 %.…”
Section: Introductionmentioning
confidence: 99%
“…So study on heterogeneous catalysts for side chain oxidation of aromatic hydrocarbons have received extensive attention. [11,12] Xu et al [13] in our group prepared EAP by oxidizing PDEB with Co/SBA-15 as the catalyst, acetic acid as the solvent and KBr as the promoter. The conversion rate of pdiethylbenzene was up to 85 %, and the yield of EAP was 58 % under the molar ratio of PDEB:KBr:H 2 O 2 :CH 3 COOH of 1:0.3 : 10.9 : 21.8 with the feed volume space velocity of 0.21 h À 1 at 85 °C for 5 h. Among them, the metal organic framework materials (MOF) [14,15] has become a research hotspot of heterogeneous catalysts [16,17] with its large specific surface area, adjustable pore structure and rich catalytic active sites.…”
Section: Introductionmentioning
confidence: 99%
“…So study on heterogeneous catalysts for side chain oxidation of aromatic hydrocarbons have received extensive attention [11,12] . Xu et al [13] . in our group prepared EAP by oxidizing PDEB with Co/SBA‐15 as the catalyst, acetic acid as the solvent and KBr as the promoter.…”
Section: Introductionmentioning
confidence: 99%